Exploring the Role of Determinants Affecting Responsible Underwater Behaviour of Marine-Based Tourists - Ke Zhang; Lewis T. O. Cheung; Theresa W. L. Lam; Anson T. H. Ma; Lincoln Fok (Behavioral Sciences, 2024)
This study utilised divers’ demographic characteristics, diving experience, and attitudes to analyse the association between these factors and divers’ responsible underwater behaviour among Chinese scuba divers in Hong Kong. More innovatively, the measurement construct of diving attitude was further employed as a mediator to investigate its influence on the relationship between divers’ diving experience and responsible underwater behaviours based on the conceptual framework of previous works in the literature. The questionnaire data for this study were collected at four of the most popular dive sites among the marine protected areas in Hong Kong, with 398 valid samples after eliminating incomplete questionnaires. Regression results demonstrated that divers’ demographic characteristics could significantly predict their responsible underwater behaviour, with age (b = 0.10, p < 0.05) and education (b = 0.15, p < 0.05) being found to be positively associated with their diving behaviour. In addition, path analysis demonstrated that divers’ diving experience and attitude could explain 13.6% and 22.6% of the variance in predicting their responsible diving behaviour, respectively. However, no mediation effect was found on the relationship between diving experience and responsible underwater behaviour relative to diving attitude, given the absence of statistical effects regarding the positive impact of divers’ diving experience on their attitude (β = 0.024, se = 0.022, t = 1.085, p = 0.279). Based on the research findings, theoretical and practical implications were discussed correspondingly, which are believed to be beneficial in promoting marine conservation and the sustainable development of marine-based nature tourism in Hong Kong.